2016
DOI: 10.1186/s13063-016-1159-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the pattern of glucocorticoid replacement on neural processing, emotional reactivity and well-being in healthy male individuals: study protocol for a randomised controlled trial

Abstract: BackgroundDeviation from the physiological glucocorticoid dynamics (circadian and underlying ultradian rhythmicity) is a common characteristic of various neuropsychiatric and endocrine disorders as well as glucocorticoid-based therapeutics. These states may be accompanied by neuropsychiatric symptomatology, suggesting continuous dynamic glucocorticoid equilibrium is essential for brain homeostasis.Methods/designThe study consists of two parts. The preliminary stage of the study aims to validate (technically an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…This study follows the guidelines for reporting fMRI data suggested by Poldrack et al (78). The ROIs for the fMRI studies have been defined a priori (60). Functional and perfusion neuroimaging data analyses were carried out using FMRIB soft-ware library 5.0 (79) and Statistical Parametric Mapping version 8, and involved a number of preprocessing and postprocessing steps (SI Appendix, Figs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study follows the guidelines for reporting fMRI data suggested by Poldrack et al (78). The ROIs for the fMRI studies have been defined a priori (60). Functional and perfusion neuroimaging data analyses were carried out using FMRIB soft-ware library 5.0 (79) and Statistical Parametric Mapping version 8, and involved a number of preprocessing and postprocessing steps (SI Appendix, Figs.…”
Section: Methodsmentioning
confidence: 99%
“…Motivated by the clinical need for improved GC-based therapeutics and the preclinical evidence, we hypothesized that under normal, nonstressful, nonpathological conditions, different ultradian GC rhythms might be translated differently in relevant GC-responsive human brain regions, and that this differential processing should be detectable using well-designed experimental protocols. We have developed a "block and replace" protocol (i.e., combined metyrapone administration with hydrocortisone infusion) in which we can reliably impose definitive patterns of plasma hydrocortisone (60). This has allowed us to provide three predetermined patterns of cortisol replacement therapy: (i) normal circadian rhythmicity lacking any physiological ultradian rhythm [s.c.-continuous hydrocortisone infusion (SCC)], (ii) normal circadian and ultradian rhythmicity [s.c.-pulsatile hydrocortisone infusion (SCP)], and (iii) current optimal oral replacement therapy (PO), characterized by suboptimal circadian and ultradian rhythms.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, based on earlier clinical work in similar experimental settings, using neuropharmacological challenge to probe psychological mechanisms of mood regulation and emotional processing, and functional neuroimaging to measure related neural activity ( Harmer et al, 2004 , Browning et al, 2007 , Murphy et al, 2008 ), we performed power calculations that confirmed a sample size of 15 participants per treatment arm, on whom complete data were available, would be required to give our study a 80% power at an alpha level of 5%. Further details on the study design and its rationale and limitations can be found in the study protocol, published elsewhere ( Kalafatakis et al, 2016b ).…”
Section: Methodsmentioning
confidence: 99%
“…We created a human model of adrenal insufficiency by pharmacologically blocking GC biosynthesis (oral administration of metyrapone three times daily) and replacing the hormone in three different modes, using either (i) oral treatment (OT), (ii) constant subcutaneous infusion (SCHI) or (iii) a novel, subcutaneous, pump-based method, delivering different size pulses of hydrocortisone every 3 h, which reproduced both the natural circadian and ultradian patterns of cortisol. We then examined the neurocognitive effects of these different GC rhythms using functional neuroimaging techniques and a set of cognitive and behavioural tests, markers of sleep behaviour, working memory and emotional processing, in a randomised, double-blind, placebo-controlled, crossover study (144). We were able to demonstrate that non-pulsatile GC exposure (i.e.…”
Section: What Do Gc Replacement Therapies Tell Us About the Significamentioning
confidence: 99%